Progress in the clinical application and research of irradiated blood - LONG Wenwei; WANG Yongjun (Zhongguo shuxue zazhi)
Irradiated blood emerged as a preventive measure for transfusion-associated graft-versus-host disease (TA-GVHD), ensuring the safety of blood transfusion for patients. In recent years, with the continuous development of transfusion medicine, the utilization rate of irradiated blood has been increasing, and there has been a growing number of studies on the effects of irradiation on blood components. Meanwhile, besides preventing TA-GVHD, irradiated blood holds promising applications in addressing other clinical transfusion issues. This article reviews the clinical applications and research of irradiated blood in transfusion medicine, aiming to provide a reference for achieving safe blood transfusion.